Tony Hunt's second sketchbook. - Hunt, Tony (Anthony) (Architectural Press, 2003)
Tony Hunt's Sketchbook illustrates the connection between brain and hand in conceiving structural concepts and details as possible solutions to structures in architecture. This new edition features 100 previously unpublished sketches. These sketches illustrate alternative structural concepts, ideas and details developed by Tony Hunt for over one hundred projects throughout his professional life. They relate directly to projects built and unbuilt in the field of structural engineering and were either produced at the time of relevant design meetings or as a response to a problem posed by an architect and are, therefore, a record of ideas proposed at the particular time. They are a source of design inspiration and an insight into the work of this well respected engineer. * Features more than sixty previously unpublished sketches * Visualise the design process through from start to finish * Gain insights into the work of this influential structural engineer.